Formoterol Thrice Weekly Does Not Result in the Development of Tolerance to Bronchoprotection - Beth E Davis; John K Reid; Donald W Cockcroft (Canadian Respiratory Journal)
BACKGROUND: Loss of bronchoprotection routinely follows regular treatment with beta2-agonists. There are no data on the effects on bronchoprotection for thrice weekly use of a beta2-agonist.